Quantum Cryptography – Principles, Protocols, and Future Directions: A Review - Dian Arif Rachman; Muhamad Akrom; Didik Hermanto; Moch. Anjas Aprihartha; Khafiizh Hastuti; Ayu Pertiwi; Purwanto (Universitas Dian Nuswantoro, 2026)
The rapid advancement of quantum computing poses a significant threat to classical cryptographic systems that rely on the computational hardness of mathematical problems such as integer factorization and discrete logarithm problems. In this context, quantum cryptography has emerged as a promising paradigm for secure communication based on the fundamental principles of quantum mechanics rather than on computational assumptions. This paper presents a comprehensive review of quantum cryptography, with a particular focus on Quantum Key Distribution (QKD), the most mature application. The study discusses the theoretical foundations of quantum security, including superposition, entanglement, and the No-cloning theorem, which collectively enable eavesdropping detection and guarantee information-theoretic security. Furthermore, the review examines major QKD protocols, such as BB84 and E91, as well as their advanced variants designed to address practical vulnerabilities and enhance performance. Recent progress in real-world implementations, including fiber-optic networks, free-space communication, and satellite-based systems such as the Micius satellite, is also analyzed. In addition, the paper highlights critical challenges related to scalability, hardware limitations, and security loopholes arising from imperfect devices. Finally, emerging research directions, including hybrid cryptographic frameworks that integrate quantum and post-quantum approaches, are discussed to provide insights into the future of secure communication. This review aims to provide a structured, up-to-date understanding of quantum cryptography, bridging the gap between theoretical developments and practical implementations, and emphasizing its crucial role in shaping next-generation cybersecurity systems.